Wisdom gained?: assessing relationships between adversity, personality and well-being among a late adolescent sample - Jayawickreme, Eranda; Brocato, Nicole W.; Blackie, Laura E.R. (Springer Verlag, 2017)
How do late adolescents make sense of stressful life events they have experienced in their lives? College students (N = 1225) reported the stressful events they had experienced in their lifetime up until the present survey, and indicated whether they considered each stressful event to be a turning point and/or an opportunity for wisdom. Students also completed measures of personality and well-being. We hypothesized that the tendency to interpret stressful events as turning points or opportunities for wisdom would explain the associations between three personality characteristics (Openness to Experience, Extraversion, and Emotionality) and well-being. We used a multi-step ESEM approach in which we first assessed the measurement structure of our items before testing partial and complete structural models. We tested partial and structural models according to extant guidelines associated with the evaluation of indirect effects models. We did not find support for the indirect effects model, but Openness was associated with the tendency to view stressful events as turning points, and Openness and Extraversion were associated with the tendency to view stressful events as leading to wisdom, as well as with increased well-being.